7, 8-Dihydroxyflavone reduces sleep during dark phase and suppresses orexin A but not orexin B in mice. (October 2015) - Feng, Pingfu; Akladious, Afaf A.; Hu, Yufen; Raslan, Yousef; Feng, James; Smith, Phillip J.
Abstract: Brain-derived neurotrophic factor (BDNF) binds to Tropomyosin-receptor-kinase B (TrkB) receptors that regulate synaptic strength and plasticity in the mammalian nervous system. 7, 8-Dihydroxyflavone (DHF) is a recently identified small molecule Trk B agonist that has been reported to ameliorate depression, attenuate the fear response, improve memory consolidation, and exert neuroprotective effects. Poor and disturbed sleep remains a symptom of major depressive disorder and most current antidepressants affect sleep. Therefore, we conducted sleep/wake recordings and concomitant measurement of brain orexins, endogenous peptides that suppress sleep, in mice for this study. Baseline polysomnograph recording was performed for 24 h followed by treatment with either 5 mg/kg of DHF or vehicle at the beginning of the dark phase. Animals were sacrificed the following day, one hour after the final treatment with DHF. Orexin A and B were quantified using ELISA and radioimmunoassay, respectively. Total sleep was significantly decreased in the DHF group, 4 h after drug administration in the dark phase, when compared with vehicle-treated animals. This difference was due to a significant decrease of non-rapid eye movement sleep, but not rapid eye movement sleep. DHF increased power of alpha and sigma bands but suppressed power of gamma band during sleep in dark phase. Interestingly, hypothalamic levels of orexin A were also significantly decreased in the DHF group (97 pg/mg) when compared with the vehicle-treated group (132 pg/mg). However, no significant differences of orexin B were observed between groups. Additionally, no change was found in immobility tests. Highlights: 7, 8-Dihydroxyflavone suppressed total sleep and NREM sleep but not REM sleep 4 h after the treatment. 7, 8-Dihydroxyflavone increased alpha and Sigma power but suppressed Gamma power. 7, 8-Dihydroxyflavone suppressed hypothalamic orexin A but not orexin B.